2021
DOI: 10.3390/jof7060454
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Aspergillus fumigatus Endocytic Trafficking within Airway Epithelial Cells Using High-Resolution Automated Quantitative Confocal Microscopy

Abstract: The precise characterization of the mechanisms modulating Aspergillus fumigatus survival within airway epithelial cells has been impaired by the lack of live-cell imaging technologies and user-friendly quantification approaches. Here we described the use of an automated image analysis pipeline to estimate the proportion of A. fumigatus spores taken up by airway epithelial cells, those contained within phagolysosomes or acidified phagosomes, along with the fungal factors contributing to these processes. Couplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 78 publications
(115 reference statements)
0
22
1
Order By: Relevance
“…In in vitro infections, epithelial uptake can lead to Af killing or, more rarely, intraphagosomal occupancy [3335, 7173]. Internalised conidia are quickly trafficked through the endosomal system to the phagolysosomes, as demostrated by the rapid acquisition of late endosomal/lysosomal markers and cathepsin D [29, 72]. Population-scale analyses further indicate that phagosomal acidification results in killing of 97-98% of the internalised conidia within 12-24 hrs, while ∼2-3% of the intracellular Af remain viable and in a third of the cases can eventually germinate by 36 h, without lysis of the host cells [29].…”
Section: Discussionmentioning
confidence: 99%
“…In in vitro infections, epithelial uptake can lead to Af killing or, more rarely, intraphagosomal occupancy [3335, 7173]. Internalised conidia are quickly trafficked through the endosomal system to the phagolysosomes, as demostrated by the rapid acquisition of late endosomal/lysosomal markers and cathepsin D [29, 72]. Population-scale analyses further indicate that phagosomal acidification results in killing of 97-98% of the internalised conidia within 12-24 hrs, while ∼2-3% of the intracellular Af remain viable and in a third of the cases can eventually germinate by 36 h, without lysis of the host cells [29].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that A. fumigatus conidia are readily internalised by AECs in vitro, with both alveolar and bronchial epithelial cells internalising 30–50% of the conidia they encounter [ 17 , 31 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 ]. In vitro A. fumigatus uptake by AECs is a time-dependent process, which increases proportionally with longer co-incubations or a higher multiplicity of infections [ 17 , 126 , 128 ]. AECs exert antifungal activity, with intracellular conidia showing impaired germination relative to extracellular conidia [ 17 , 126 ].…”
Section: Are Airway Respiratory Cells Internalising a Fumig...mentioning
confidence: 99%
“…Among these 8 TFKOs, only 4 TF-encoding genes have been previously characterised. This includes HapX (AFUB_052420), a component of the CCAAT-binding complex (Hortschansky et al ., 2017) which is involved in iron acquisition and metabolism in Aspergillus (Gsaller et al ., 2014), PacC (AFUB_037210) previously reported to regulate A. fumigatus epithelial invasion (Bertuzzi et al ., 2014), Ace1/SltA (AFUB_041100) which regulates conidial formation including cell wall architecture and secretion of mycotoxins and secondary metabolites (H. Liu et al ., 2021) and AtfD (AFUB_078150) which is involved in conidial stress responses (Silva, Horta and Goldman, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with such functionality, the colonial phenotypes of all four mutants exhibit compact morphology (Fig 3 and Fig 6). It is therefore feasible that the secondary metabolite composition of the spores of these mutants differs sufficiently from that of the parental isolate to cause deficits in epithelial detachment, either via aberrancies in one or several of contact-mediated toxicity, epithelial uptake of and phagolysomal fusion, the latter of which has recently been shown to determine efficiency of intracellular fungal killing (Ben-Ghazzi et al, 2021). Remarkably, TFKOs that are deficient in causing epithelial cell lysis universally exhibit culture filtrates that are less cytolytic than the parental progenitor (Fig7).…”
Section: Discussionmentioning
confidence: 99%